Definição de marcadores químicos por acompanhamento do processamento térmico e ultrassom de ponteira de suco de maracujá - Soares, Márcia Valéria Lacerda (2015)
Brazil has a great biodiversity, which should be explored and transformed into food and products to be consumed. Among existing species of passion fruit, only three are used by industry and among these, exclusively the Passiflora edulis serves the food market, because this species has very attractive sensory attributes,also is related to several benefits to improvhealth. However, the fruit characteristics “in natura” are not always maintainedthem after processing. Thus, this study aims to evaluate the metabolic profile present in passion fruit juice after heat treatment of sterilization further morepasteurization in different conditions of time and temperature and still submit the juice without heat treatment to a ultrasoundprocessing. The studied variables in heat processing wereretentiontime (0, 4, 15, 30 and 60 seconds), temperature (85 and 140 °C) and the non-thermal ultrasound process withpower (50.000, 75.000 e 100.000 W/L) and time (1, 2.5 and 5 minutes). For the extraction of the compounds were used methanol, and sample identification performed in LC-MS. Also was carried out Nuclear Magnetic Resonance analysis (NMR) andTotal Extractable Polyphenols (TEP). In the methodology employed for processing with ultrasound, the samples were subjected to different power and time. Then, was performed the same reading and extracting methodology used for heat processing. For treatment of the data was performed Principal Component Analysis (PCA) for LC-MS and NMR, the polyphenols were analyzed by the method described by Singleton and Rossi (1965), with adaptations. The results were compared to a control sample (no treatment). Were found 32 chromatographic peaks, of which 4 were degraded, 12 were formed and 16 remained unchanged. With increasing temperature, there was degradation of phenolic compounds. The heat process can be controlled from data obtained on the passion fruit juice profile submitted to heat treatment